Women Entrepreneurship among Minorities in India - Sultana, H. Yasmeen; Sankaran, A.; Jamal, M. Abdul; Sama, A. (International Journal of Psychosocial Rehabilitation, 2020)
The role of entrepreneur in an economy is to create an environment which is conducive to the optimum utilization of the available resources such as money, man power or material. The emergence of women entrepreneurs and their contribution to the national economy is quite visible in India. The number of women entrepreneurs has grown over a period of time, especially in the 1990s. Women entrepreneurs need to be lauded for their increased utilization of modern technology, increased investments, finding a niche in the export market, creating a sizeable employment for others, and setting the trend for other women entrepreneurs in the organized sector. According to government reports, Muslim women are among the poorest, educationally disenfranchised, economically vulnerable, politically marginalized group in the country. Most Muslim women remain “invisible” workers in the informal economy. The minority Muslim community was specifically targeted as historically, they have been one of the most backward, poor and marginalized communities in India. The present study is an attempt to assess the entrepreneurship development among Muslim community in Chennai city. As this study is focusing on only the Muslim community, it is displayed the existing entrepreneurial spirit among this community, nature of their business and available support system particularly in Chennai city. The present study conducted in Chennai city particularly places where Muslim women are involving in the entrepreneurial activities. In order to execute this research, both the primary and secondary data has been used. Secondary data have been collected from the published reports and materials while primary data have been collected from 300 muslim women entrepreneurs as a sample respondents from simple random sampling method. The data were analyzed quantitatively and qualitatively. This study has helped to recognize the innumerable constraints which the muslim women entrepreneurs of our research area have faced. The women entrepreneurs of both the areas (Financially and socially) faced the constraints of similar nature. The proportion was definitely different but the nature of the problem was more or less the same. The basic requirement of muslim women entrepreneur is starting a venture is the raising of funds. This study draw out that there was correspondence in the constraints faced by the women entrepreneurs of both the areas while running a business.